2016
DOI: 10.3748/wjg.v22.i10.2900
|View full text |Cite
|
Sign up to set email alerts
|

Update on a tumor-associated NADH oxidase in gastric cancer cell growth

Abstract: Gastric cancer is one of the most common human malignancies, and its prevalence has been shown to be well-correlated with cancer-related deaths worldwide. Regrettably, the poor prognosis of this disease is mainly due to its late diagnosis at advanced stages after the cancer has already metastasized. Recent research has emphasized the identification of cancer biomarkers in the hope of diagnosing cancer early and designing targeted therapies to reverse cancer progression. One member of a family of growth-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Interestingly, the responsiveness toward oxaliplatin in these cell lines corresponded to both their p53 functionality and the expression level of tumor-associated NADH oxidase (tNOX) [ 9 ]. tNOX catalyzes the conversion of reduced NADH to oxidized NAD + ; it universally expressed in a wide range of transformed/cancerous lines and is positively correlated with cell growth ability [ 10 13 ]. Numerous anticancer drugs (oxaliplatin, capsaicin, doxorubicin and its derivatives, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the responsiveness toward oxaliplatin in these cell lines corresponded to both their p53 functionality and the expression level of tumor-associated NADH oxidase (tNOX) [ 9 ]. tNOX catalyzes the conversion of reduced NADH to oxidized NAD + ; it universally expressed in a wide range of transformed/cancerous lines and is positively correlated with cell growth ability [ 10 13 ]. Numerous anticancer drugs (oxaliplatin, capsaicin, doxorubicin and its derivatives, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Several isoforms of VDACs were identified that have different reactive sulfhydryl groups [58], but at least two sulfhydryl groups are conserved in all isoforms and may serve in thiol-disulfide exchange [59]. Surprisingly, the redox activity of VDAC is controlled by growth hormones [60], and even more interesting, transformed tumor cells have expressed a different NADH oxidase (tNOX) and a different VDAC (VDAC2) [61]. For this reason HeLa cells as used by Friedman et al may not be representative for NOX/VDAC mediated activities.…”
Section: Vdac As a New Origin Of Emf-induced Effectsmentioning
confidence: 99%
“…In addition, tolerated oxidative stress in cancer is a consequence of increased basal metabolic activity and peroxisome activity, uncontrolled growth factors of cytokine signaling, oncogene activity, and enhanced activity of oxidase and oxygenase enzymes such as NADPH oxidase complex (NOX), cyclooxygenases, and lipoxygenases [24,25]. Cancer cells also express on their surface a unique tumor-associated hydroquinone (NADH) oxidase with protein disulfide-thiol exchange activity (tNOX/ENOX2), which contributes to the generation of ROS (mainly superoxide) and induction of oxidative stress [26,27]. This protein marker is a subject of interest in our study.…”
Section: Introductionmentioning
confidence: 99%